2007
DOI: 10.1002/ijc.22778
|View full text |Cite
|
Sign up to set email alerts
|

Coffee consumption and risk of colorectal cancer in a population‐based prospective cohort of Japanese men and women

Abstract: We prospectively examined the association between coffee consumption and the risk of developing colorectal cancer in a large population-based cohort study (the JPHC Study) of Japanese men and women. Data were analyzed from a population-based cohort of 96,162 subjects (46,023 men and 50,139 women). A total of 1,163 incident colorectal cancers were identified during the followup period, including 763 cases of colon cancer and 400 of rectal cancer. We observed a significant inverse association between coffee cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 37 publications
5
76
0
Order By: Relevance
“…If the study sample was found to overlap with that in another article or if two articles described aspects of the same study, only the publication with the largest sample was used (10)(11)(12)(13)(14)(15)(16)(17)(18) . If a study provided several OR/RR, we extracted the one reflecting the greatest degree of control for potential confounders (17,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) . To assess a summary OR/RR for colorectal cancer in both sexes, we used combined estimates if provided.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…If the study sample was found to overlap with that in another article or if two articles described aspects of the same study, only the publication with the largest sample was used (10)(11)(12)(13)(14)(15)(16)(17)(18) . If a study provided several OR/RR, we extracted the one reflecting the greatest degree of control for potential confounders (17,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) . To assess a summary OR/RR for colorectal cancer in both sexes, we used combined estimates if provided.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…The first consisted of 96,162 Japanese men and women, and 1163 incident cases of colorectal cancer [111]. There was no statistically significant association between green tea consumption and incidence of colon and rectal cancers combined or separately in either men or women or both.…”
Section: Cancermentioning
confidence: 98%
“…There were two recent prospective studies on green tea consumption and colorectal cancer incidence and mortality in Japan [111,112]. The first consisted of 96,162 Japanese men and women, and 1163 incident cases of colorectal cancer [111].…”
Section: Cancermentioning
confidence: 99%
“…However, its effects on human health are not well understood. Some studies suggested that coffee consumption had preventive properties for metabolic diseases, such as type 2 diabetes [40,41], or cancers, such as hepatocellular carcinoma [42,43] and colorectal cancer [44,45], through its content of potentially antimutagenic substances [46]. These findings led to the hypothesis that coffee consumption lowers the risk of some types of cancers.…”
Section: Coffee and 8-oxo-gua / Ogg1mentioning
confidence: 99%